2019
DOI: 10.1002/hep.30779
|View full text |Cite
|
Sign up to set email alerts
|

Quality Measures, All‐Cause Mortality, and Health Care Use in a National Cohort of Veterans With Cirrhosis

Abstract: Decompensated cirrhosis is associated with high morbidity and mortality. However, no standardized quality measures (QMs) have yet been adopted widely. The Veterans Affairs (VA) Advanced Liver Disease Technical Advisory Group recently developed a set of six internal QMs to guide quality improvement efforts in cirrhosis in the domains of access to care, hepatocellular carcinoma surveillance, variceal surveillance, quality of inpatient care for upper gastrointestinal bleeding, and cirrhosis‐related rehospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…(4,5) Multiple studies in liver disease have shown that access to specialty care improves adherence to guideline-recommended care for liver disease and clinical outcomes such as readmissions and mortality. (6)(7)(8) Rooted in this prior research, the goal of our program was to improve access to care for advanced liver disease, which has a comparable morbidity and mortality to end-stage congestive heart failure and chronic obstructive pulmonary disease. (9) The tertiary care team partnered with a large, community-based gastroenterology (GI) practice of 23 health care providers located in Lancaster, Pennsylvania, about 60 miles from the downtown University hospital.…”
Section: Introductionmentioning
confidence: 99%
“…(4,5) Multiple studies in liver disease have shown that access to specialty care improves adherence to guideline-recommended care for liver disease and clinical outcomes such as readmissions and mortality. (6)(7)(8) Rooted in this prior research, the goal of our program was to improve access to care for advanced liver disease, which has a comparable morbidity and mortality to end-stage congestive heart failure and chronic obstructive pulmonary disease. (9) The tertiary care team partnered with a large, community-based gastroenterology (GI) practice of 23 health care providers located in Lancaster, Pennsylvania, about 60 miles from the downtown University hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were classified as having received liver imaging if they underwent at least one abdominal ultrasound or contrast‐enhanced computed tomography (CT) or magnetic resonance (MR) study for 2 years following the index HBsAg + result. We evaluated HCC surveillance in screening candidates: age ≥40 years OR any age with cirrhosis, 5,27 calculating the proportion of total follow‐up time during which patients were adherent to annual or biannual screening intervals with appropriate liver imaging (ultrasound, contrast‐enhanced CT or MRI) as per our previous work 28,29 . A grace period of 30 days was accounted for in adherence calculations 29 .…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated HCC surveillance in screening candidates: age ≥40 years OR any age with cirrhosis, 5,27 calculating the proportion of total follow‐up time during which patients were adherent to annual or biannual screening intervals with appropriate liver imaging (ultrasound, contrast‐enhanced CT or MRI) as per our previous work 28,29 . A grace period of 30 days was accounted for in adherence calculations 29 . Outpatient pharmacy data were used to determine whether patients were prescribed antiviral therapy with oral nucleoside analogs such as interferon‐alpha, lamivudine, adefovir, telbivudine, entecavir or tenofovir.…”
Section: Methodsmentioning
confidence: 99%
“…( 14 ) Adherence to HCC surveillance for patients with cirrhosis in the VHA is estimated at only 42%. ( 15 ) The reasons for this low rate are unclear. Access to gastroenterology and hepatology in the VHA is associated with higher reported rates of surveillance, but rates are still low despite most centers now offering these specialists.…”
mentioning
confidence: 99%